Obtaining FMEA’s indices for occupational safety in civil construction: a theoretical contribution - Cavaignac, Andre Luis De Oliveira; Uchoa, Jhelison Gabriel Lima (Brazilian Journal of Operations & Production Management, 2018)
Highlights: 1- Severity, occurrence and detection indices were obtained for specific use in construction safety; 2- Important theoretical contribution to the use of FMEA in safety of construction work; 3- Obtaining the S, O and D indices better suited to civil construction will encourage the use of FMEA in the area; 4- A quick reference table of S, O and D indexes was proposed for use by occupational safety professionals; 5- The quick reference table will allow the RPNs of the fault modes to be safely compared between different situations and different applicators. Goal: The achievement of FMEA indices better adapted to the area of occupational safety in construction. From a quick reference table, the use of the FMEA will be facilitated by professionals in the area. Design / Methodology / Approach: For the elaboration of this work were carried out researches in the literature available in scientific journals on the subject. To obtain the severity tables, the conversion of concepts of maintenance and reliability to concepts of accident severity was performed. For the occurrence table the Ford Handbook model was used (FORD, 2011), and as the database of accident statistics the most up-to-date social security yearbook was used (FAZENDA, 2016). For the detection table, a detection index model was proposed that was discussed based on commonly used risk management procedures and tools. Results: Individual tables were obtained for each FMEA index. The indices were adapted to the reality of the application of FMEA in work safety in construction. From the individual tables, a quick reference table containing the three FMEA indices related to the qualitative scale of each was obtained. Limitations of the investigation: The study limits itself to adapting the FMEA indices for work safety in construction. This study may serve as a basis for future studies on obtaining the FMEA indexes for work safety applied in other areas of activities, requiring adequate scientific sources. Regarding the validation of the indices, it is noticeable the difficulty of comparing these indices proposed in this work with indices applied subjectively and without scientific reference, relying only on the skill and previous experience of the applicator. However, it is reasonable to say that the FMEAS applied with the indices obtained in this work will have a better accuracy in representing the reality, regardless of the applicator's ability. Practical implications: Reduce the difficulties in choosing the S, O and D indices for the application of FMEA in construction safety, reduce the inaccuracy in obtaining the risk priority number for failure modes and diffuse the use of FMEA for risk analysis and prevention occupations in construction are the main theoretical implications of this work. Originality / Value: there are studies in the literature on the application of FMEA in various areas - maintenance and product development, for example - but there is very little research on the application of FMEA in occupational safety. In addition, FMEA application studies cite the difficulty of choosing the S, O and D indices, but there is an absence of studies seeking solutions to this imprecision. In this sense, this work seeks to contribute to a choice of the FMEA indexes, which is easier and more efficient due to the better adaptation of the same to the occupational safety area in civil construction.